De nouvelles obligations règlementaires pour l'approche écosystémique : une démarche de planification globale au service de l'aménagement des villes favorables à la santé-environnement - Shireen Nazer (VertigO)
This paper presents a critical analysis of how to develop the territories. Whether in Palestine or France, the ecosystem approach should be highlighted in order to create cities both sustainable and livable. They should provide a balanced environment for its people: drinking water, breathing air, healthy and sufficient food to eat... All these parameters are the core values of public health. Here we find the questions related to agriculture and food insecurity, poverty and mortality, chronic diseases and pollution, environmental degradation... These interrelated themes are connected to the complexity of spatial organization and the level of services provided. They can't be solved without a global vision and a high-dimensional planning that takes into account the human and his well-being. The ecosystem approach to health posed a methodological framework for analyzing Rennes and Palestinian territories despite the convergent differences between the two territories. Whatever the social, economical and environmental differences, cities must be part of an overall system that goes beyond the conventional planning and sectorial boundaries and national borders.